Dynamic behaviors of multiple-solitons in a magnetized dusty plasma - Salam, Md. Abdus; Ali, M. Zulfikar; İnç, Mustafa; Akbar, M. Ali (Pergamon-Elsevier Science Ltd, 2022)
[Abstract Not Available]
Keywords: Multiple-soliton solutions; Magnetized dusty plasma; Cole-Holf transformation; Simplified Hirota method; Reductive perturbation method